2022
DOI: 10.4269/ajtmh.21-0719
|View full text |Cite
|
Sign up to set email alerts
|

Chikungunya Virus Infects the Heart and Induces Heart-Specific Transcriptional Changes in an Immunodeficient Mouse Model of Infection

Abstract: Chikungunya virus (CHIKV) is a mosquito-transmitted pathogen in family Togaviridae, genus Alphavirus. Although CHIKV is well known for its ability to cause debilitating rheumatoid-like arthritis, it has been also been observed to cause cardiovascular symptoms such as arrhythmias. Here, using samples from a previous study, we sequenced RNA from serum, kidney, skeletal muscle, and cardiac muscle from CHIKV- and mock-infected IFN-αR−/− mice using two sequencing techniques to investigate heart-specific changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…We used ViReMa to identify DVGs, as this algorithm has been developed and validated to faithfully identify recombination events in a range of plant viruses ( 65 67 ), insect viruses ( 68 , 69 ), arthropod-borne viruses (arboviruses) ( 70 72 ), human pathogens (influenza virus [ 73 ], reovirus [ 74 ], MERS-CoV, and SARS-CoV-2 [ 17 , 75 ]), and retroviruses (human immunodeficiency virus [HIV]) ( 76 ). It has also been validated independently by Alnaji et al ( 77 ) and Boussier et al ( 78 ) who provided a series of condition and parameter optimizations using simulated and experimental data to map RNA recombination events in DVGs of influenza A and B.…”
Section: Discussionmentioning
confidence: 99%
“…We used ViReMa to identify DVGs, as this algorithm has been developed and validated to faithfully identify recombination events in a range of plant viruses ( 65 67 ), insect viruses ( 68 , 69 ), arthropod-borne viruses (arboviruses) ( 70 72 ), human pathogens (influenza virus [ 73 ], reovirus [ 74 ], MERS-CoV, and SARS-CoV-2 [ 17 , 75 ]), and retroviruses (human immunodeficiency virus [HIV]) ( 76 ). It has also been validated independently by Alnaji et al ( 77 ) and Boussier et al ( 78 ) who provided a series of condition and parameter optimizations using simulated and experimental data to map RNA recombination events in DVGs of influenza A and B.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies, including our own, reported the presence of infectious particles or viral RNA in the cardiac tissue of CHIKV-infected mice (Clavarino et al, 2012;Langsjoen et al, 2021;Noval et al, 2019). However, in these studies, mice were not perfused, thus confounding measurements due to the potential presence of the virus originating from serum in CHIKVinfected hearts.…”
Section: Discussionmentioning
confidence: 91%
“…In some patients, cardiac symptoms are primarily related to CHIK infection; however, in others, cardiovascular disease may be secondary to pre-existing comorbidities 3 . Animal models have revealed active replication of CHIKV in the hearts of immunodeficient mice, and human biopsies have shown CHIKV in the myocardium, suggesting that direct viral infection plays a pathogenic role in CHIK cardiac disease 18,19 .…”
Section: Cardiovascular Manifestationsmentioning
confidence: 99%